Inheritance of aluminium tolerance in sunflower (Helianthus annuus L.): Inheritance of aluminium tolerance in sunflower (Helianthus annuus L.) - VIVEK K SINGH,; SUBHASH CHANDER,; ANU,; R K SHEORAN, (Journal of Oilseeds Research, 2023)
In acidic soil, aluminium (Al) toxicity is one of the foremost restraining factors which inhibit crop performance. Breeding for Al tolerance seems to be a vital approach for enhancing productivity of field crops including sunflower in acidic soil regions. In order to understand the inheritance pattern, tolerant genotypes NDLR-06 and EC601861 were crossed with susceptible genotypes MR-06 and RHA-298. P1, P2, F1, F2 and backcross populations were raised in nutrient solution and classified as tolerant/susceptible by observing root re-growth after staining with eriochrome cyanine R. Dominance nature of Al tolerance over susceptible was confirmed by the responses of F1’s which were similar to the tolerant parents. The segregation ratio for Al tolerance vs. susceptible in the F2 and backcross generations were 3:1 and 1:1, respectively. These outcomes indicated that inheritance of Al tolerance is governed by single dominant gene which can be transferred easily to desirable genotypes via backcross breeding method. This is the first report on inheritance of Al tolerance in sunflower.